Inequality and structural transformation in the changing nature of work: The case of Indonesia - Arief Anshory Yusuf; Putri Riswani Halim (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper analyses the labour market dynamics in Indonesia from 2001 to 2015 and explores the role of the changing nature of occupational employment in explaining the rising earnings inequality during the same period. First, we find evidence of a disproportionate increase in the returns to tertiary education, the increasing shares of highly skilled and elementary workers, and a sign of job polarization. Second, we find evidence of job polarization in the periods 2005-10 and 2005-15. Third, using reference influence function regressions, we quantify the extent to which changes in inequality over time can be attributed to changes in the distributions of worker characteristics and changes in the returns to these characteristics. The results suggest that in all the periods where Gini of earning is rising, the changing earnings structure, most notably returns to education, residency, and possibly routine-task intensity, contributes to the rise.
Keywords: J21; J24; D63; 330; labour market dynamics; inequality; occupational employment; earnings inequality